Taxonomic notes on the nursery-web spider genus Dendrolycosa Doleschall, 1859 (Araneae: Pisauridae) from India, with the description of a new species - Sudhin, Puthoor Pattammal; Sen, Souvik; Jäger, Peter (Zootaxa, 2023)
A new species of the nursery-web spider genus Dendrolycosa Doleschall, 1859, D. sahyadriensis spec. nov. (♂♀) is described from the Mookambika Wildlife Sanctuary, Karnataka, India. Detailed morphological descriptions, diagnoses and illustrations of the copulatory organs of both sexes are provided. The status of the Dendrolycosa species in India is also given, along with a distribution map.